The influence of an electron beam on the frequency of appearance of modifications and mutagens in the residual florula - Antipov, V.S.; Babych, E.M.; Berezhna, I.V.; Hirna, T.V.; Kornilov, E.O.; Kiselev, V.A.; Linnik, A.F.; Sklar, N.I.; Uskov, V.V. (Вопросы атомной науки и техники, 2006)
We have carried out a series of tests for studying an electron beam (Е=4 МеV) influence on adaptive mutability test cultures of the sanitary-model microflora in various regimes (0.4…3.2 kGy) of processing samples of natural water and sewages. Mutafacient properties and modifications of the residual microflora stimulated by the electron beam effect are scarcely pronounced. They do not indicate themselves in the regimes that guarantee the water purification up to the indices stipulated by the corresponding standards.